A Diagnostic and Therapeutic Hydrogel to Promote Vascularization via Blood Sugar Reduction for Wound Healing (Adv. Funct. Mater. 14/2023). (4th April 2023) - Han, Xiaoyu; Chen, Shuyu; Cai, Zhengwei; Zhu, Ying; Yi, Weiwei; Guan, Mengtong; Liao, Bo; Zhang, Ying; Shen, Jieliang; Cui, Wenguo; Bai, Dingqun
Abstract : Vascularization In article number 2213008, Dingqun Bai, Wenguo Cui, Jieliang Shen and co‐workers use the Schiff base reaction to construct an innovative diagnostic and therapeutic hydrogel system. While the nanozyme consumes glucose, the concentration of glucose is monitored in real time, and the system delivers vascular endothelial growth factor through ultrasound in a precise and non‐invasive way to promote diabetic wound healing.